Detection of phytoplasma in citrus orchards of Pakistan - Nadeem Chohan, Paul Holford, Shazia Mannan, Muhammad Ibrahim, Shahid (Journal of Phytology, 2009)
Citrus fruits are one of the major export commodities of Pakistan. However, being such an important crop citrus is affected by a number of destructive diseases and phytoplasmal disease is one of them. In Pakistan no significant research has been conducted on phytoplasmal diseases of citrus. Therefore, present study was conducted to confirm the presence of phytoplasmal particles in diseased samples of citrus from Sahiwal, Pakpattan, Multan and Khaenwal districts the most important citrus growing areas of Pakistan. For this purpose DNA was extracted from leaf samples collected from the three districts and single (O-MLO) and nested PCR were applied to detect phytoplasmal particles. With O-MLO primers a 558bp fragment was amplified from 16S rRNA phytoplasmal gene and 1.2kb phytoplasmal DNA fragment was amplified with nested PCR. The results revealed the presence of citrus phytoplasma in Southern Punjab region of Pakistan. In order to confirm the alternate hosts of citrus phytoplasma as well as the insect vectors involved in the transmission of the disease, weeds as well as insects were collected from citrus orchards for molecular detection of phytoplasma and their analysis are is in progress.